Transformation of the Short Story Blokeng by Ahmad Tohari into a Drama Performance and Its Implications for Drama Appreciation Lectures - Windari, Essy Yunita; Hayati, Yenni (JOLLT Journal of Languages and Language Teaching, 2024)
Transformation occurs when one type of art is replaced by another. Literary works can not only be translated, or transmitted from one language of work to another, but can also be translated into other forms of art. This research aims to describe the transformation of the short story Blokeng by Ahmad Tohari into a drama performance. The theory used is Rifaterre and Pradotokusumo's transformation theory. This research method is descriptive qualitative. The research results show that there are two transformation processes that occur. First, five data were found in the form of expansion or additions to the plot and characters of the short story Blokeng by Ahmad Tohari in drama performances. Second, two modified data were found from the short story Blokeng by Ahmad Tohari for drama performances. Third, there are seven things from the research results regarding the transformation of short stories into drama performances that can be applied to the Drama Appreciation course. The creation of an adapted drama performance as a form of change in a literary work may result in several differences from the work that is the reference. Thus, in the process of adapting a literary work into a drama performance, one should still pay attention to the meaning of the story, so that the audience still gets a thorough understanding of the essence of the literary work when the transformation process occurs from what was originally a textual media then converted into an audio-visual media. or vice versa. Theoretically, this research contributes to providing knowledge to readers about the transformation of the short story Blokeng by Ahmad tohari into the drama performance. Furthermore, it is hoped that teaching materials will be produced that is useful for the Drama Appreciation course.